University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 3 - Section 3.2 - The Derivative as a Function - Exercises: 2

Answer

$-4$ $-2$ $2$

Work Step by Step

$F(x)=(x-1)^2+1=x^2-2x+2$, therefore $F'(x)=2x-2+0=2x-2$ Therefore: $F'(-1)=2\times(-1)-2=-4$. $F'(0)=2\times(0)-2=-2$ $F'(2)=2\times(2)-2=2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.